Assessment of Multi-attribute Flood Risk in the Pearl River Basin Considering the Reasonable Service Life of the Project - WANG Hanye; HUANG Shengzhi; WANG Lu; FANG Wei (Renmin Zhujiang)
Flood is characterized by flood peak, flood volume and duration. The impact of theproject's reasonable service life was ignored in previous flood risk assessment. And the riskindex considering reasonable service life of the project can better describe the flood riskundertaken by the projects. Based on this, this paper adopts the daily flow data of typicalhydrological stations in the Pearl River Basin from 1997 to 2017, and selects floods by the peaksover threshold method to enrich the flood samples, builds the joint distribution function of floodpeak and volume by Copula function, calculates the joint return period, and builds the flood riskindex with consideration of the joint return period and the reasonable service life of project.The results show that: ① Under the combination of flood peak and flood volume in the same returnperiod, compared with other stations, the risk of flood with high peak or large volume is thehighest in Yujiang River, while risk of flood with high peak and large volume is the highest inLiujiang River (except 10-year return period); ② When the reasonable service life of Type I largewater conservancy project (dam, n=50~100 years) is considered, the risk of flood with high peakor large volume is the highest in Xijiang River; and ③ The risk of flood with high peak and largevolume exceeding the design value is the highest in Liujiang River.